Analysis and evaluation of political violence against indigenous women in the State of Oaxaca in the period 2020-2022 - Apreza Salgado, Socorro (2024)
The purpose of this article is to review the scope of the regulatory framework to curb gender-based political violence against indigenous women in Mexico and particularly in the state of Oaxaca. It is concluded that despite the legal transformations and procedures through which attempts have been made to address the problem, there is currently no adequate statistical information that is easily accessible to the public, to accurately measure the impact on structural violence to which indigenous women are subjected. The construction of diagnoses and public policies is proposed under dynamics of horizontal participation with a perspective of legal pluralism and interlegality, in order to enable a broad dialogue between Western law and the radical struggles and transformations that indigenous women claim in their own processes and legal systems.